Cell Wall Invertase and Sugar Transporters Are Differentially Activated in Tomato Styles and Ovaries During Pollination and Fertilization - Shen, Si; Ma, Si; Liu, Yonghua; Liao, Shengjin; Li, Jun; Wu, Limin; Kartika, Dewi; Mock, Hans-Peter; Ruan, Yong-Ling (Frontiers in Plant Science, 2019)
Flowering plants depend on pollination and fertilization to activate the transition from ovule to seed and ovary to fruit, namely seed and fruit set, key for completing plant life cycle and realizing crop yield potential. These processes are highly energy-consuming and rely on the efficient use of sucrose as the major nutrient and energy source. However, it remains elusive as how sucrose import into and utilization within the female reproductive organ are regulated in response to pollination and fertilization. Here, we explored this issue in tomato by focusing on genes encoding cell wall invertase (CWIN) and sugar transporters, major players in sucrose phloem unloading and sink development. In comparison with that in the non-pollination control, the transcript level of a major CWIN gene, LIN5 and the CWIN activity were significantly increased in style at 4 hours after pollination (HAP) and sustained at 2 days after pollination (DAP). In the ovaries, however, CWIN activity and LIN5 expression did not increase until 2 DAP when fertilization occurred. Interestingly, a CWIN inhibitor gene INVINH1 was repressed in the pollinated style at 2 DAP. In response to pollination, the style exhibited increased expressions of genes encoding hexose transporters, SlHT1, 2, SlSWEET5b, and sucrose transporters SlSUT1, 2 and 4 from 4 HAP to 2 DAP. Upon fertilization, SlSUT1 and SlHT1, 2, but not SlSWEETs, were also stimulated in fruitlets at 2 DAP. Together, the findings reveal that styles respond promptly and more broadly to pollination for activation of CWIN and sugar transporters to fuel pollen tube elongation, whereas the ovaries do not exhibit activation for some of these genes until fertilization occurs.